The Diagnostic Effect of Intraoperative Indocyanine Green Imaging for Endometriosis: A Systematic Review and Meta-Analysis - Yuan Zhuang; Honghui Ou; Yue Xu; Hua Yang (IMR Press, 2024)
Background: To comprehensively investigate the diagnostic effect of intraoperative indocyanine green (ICG) imaging for endometriosis (EMs). Methods: We systematically retrieved relevant literature from a series of databases (Embase, Web of Science, PubMed, Clinical Trials, Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), and WanFang Database) up to January 2024. We also performed manual searches using the reference lists from selected articles, along with reports from relevant meetings and Google Scholar. Data were stored and analyzed by Review Manager version 5.3 and Stata/MP version 14.0. Results: Systematic searches of the literature identified six articles comparing the diagnostic effect of ICG imaging to white light (WL) imaging for EMs during laparoscopic surgery. Two of these studies found that ICG imaging improved the diagnostic rate of EMs while the remaining four studies reported that the diagnostic value of ICG imaging was minimal. Cumulative analysis determined that the sensitivity was 0.88 (95% confidence interval [95% CI]: 0.81-0.93) for WL and 0.64 (95% CI: 0.36-0.84) for ICG. The specificity was 0.85 (95% CI: 0.49-0.97) for WL and 0.88 (95% CI: 0.66-0.97) for ICG. The positive likelihood ratio (LR+) was 5.8 (95% CI: 1.4-24.5) for WL and 5.4 (95% CI: 1.2-24.1) for ICG. The negative likelihood ratio (LR-) was 0.14 (95% CI: 0.09-0.20) for WL and 0.41 (95% CI: 0.18-0.94) for ICG, while the diagnostic odds ratio (DOR) was 42 (95% CI: 10-182) for WL and 13 (95% CI: 1-124) for ICG. Conclusions: Although we only analyzed a limited number of publications, our analysis demonstrated that ICG may be helpful for the visualization of occult EMs, although the diagnostic effect of ICG is not superior to WL. Our findings need to be confirmed by additional studies involving larger sample sizes from multiple centers.